An Evaluation of The Nutritional Quality Evaluation of Three Cultivars of Syzygium samarangense Under Malaysian Conditions - Moneruzzaman, K.M.; Boyce, A.N.; Normaniza, O.; Hossain, A.; Alebidi, A.I.; Al-Saif, A.M. (2011)
A study was carried out to selected physiological and biochemical characteristics of Syzygium samarangense for their physiological and biochemical characteristics at Functional Food Laboratory, University of Malaya, Kuala Lumpur. Various physiological and biochemical parameters were monitored during two seasons of fruit growth between October, 2009 to August, 2010 with the 'Giant green', 'Masam manis pink' and 'Jambu madu red' cultivars of S. samarangense. Ripened fruits of the different cultivars were collected from the experimental field of Banting, Selangor and analyzed for selected physiological parameters namely chlorophyll fluorescence, quantum yield, fruit weight, total yield, number of seed per fruit, seed weight and dry matter content and some biochemical parameters that is, juice content, pH, total soluble solids (TSS), glucose, fructose, inverted sugar, ethanol, total flavonoids, phenols and anthocyanins content. It was observed that highest chlorophyll fluorescence, maximum quantum yield (0.79), fruit weight, seed number (4) and seed weight per fruit (4.56 g) were in the 'Giant Green' cultivar while total yield, glucose (9.83%), fructose (9.9%), inverted sugar (9.57%), ethanol (20.5%), flavonoids (914.1 mg/100g) and phenols (326.67 mg GAE/100g) were in the 'Masam manis pink' cultivar, and the highest juice content (76.33 ml), highest total soluble solids (8.76 degrees Brix) and anthocyanins (2.78 mg/L) were in the 'Jambu madu Red' cultivar. From this study, it can be concluded that 'Masam manis pink' and 'Jambu madu red' cultivar are comparatively better than 'Giant green' cultivar under South Asian conditions.